FRANZ KAFKA’S ROLE IN GERMAN LITERATURE (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
The article discusses Franz Kafka’s writing style, literary views and his unique plase in world literature. In particular, his poetry and stories differ from other ortists of that period by their abnormal and grotesque style and ideas.